Analisis Statistik Deskriptif Karakteristik Demografi dan Akademik(Usia, IP, dan Organisasi) Mahasiswa FIP UNIMED - Sibarani, Greyscia Hotmauli; Silalahi, Wilde Dosta Cristina; Dalimuthe, Indah Pefrianti; Sihaloho, Elovani Dea Ananda; Silalahi, Tsalitsa Gunawan; Sihite, Erika (Veritas: Jurnal Penalaran dan Riset Mahasiswa Pendidikan, 2025)
This mini-research aims to present a descriptive statistical analysis of data collected from students, focusing on the characteristics of respondents and the variables studied, as a fulfillment of the Statistics course assignment. This study uses a quantitative approach with a sample of 32 respondents, consisting of 28 females and 4 males, who were selected purposively. Data collection was carried out using a validated Google Form-based questionnaire. The collected data were then analyzed using descriptive statistics, including calculating frequencies, percentages, means, and standard deviations. The results of the frequency analysis show that the majority of respondents were females (87.5%) and came from the 2023 batch (53.1%). The majority of respondents came from the PGSD Department (40.6%), followed by BK (25.0%), PENMAS (18.8%), and PGPAUD (15.6%). The average age of respondents who were active in organizations (YES) was 19.6 years, while those who were not active (NO) was 19.5 years. The age range of the respondents was 19 years, with 10 respondents actively participating in organizations and 1 respondent inactive. Based on GPA, the most common GPA among respondents was 3.6 and 3.7. Overall, this report provides a comprehensive overview of the respondents' demographics and their distribution across the variables studied using descriptive statistical techniques. It is hoped that this report will provide benefits and contribute positively to the development of science at Medan State University.